The molecular genetic basis of Glanzmann thrombasthenia in the Iraqi-Jewish and Arab populations in Israel. - Newman, P J (1991)
Glanzmann thrombasthenia is an autosomal recessive bleeding disorder characterized by a decrease or absence of functional platelet glycoprotein (GP) IIb-IIIa (alpha IIb beta 3) integrin receptors. Although thrombasthenia is a rare disorder, its occurrence is increased in some regions of the world where intracommunity marriage and consanguinity are commonplace, resulting in increased expression of autosomal recessive traits. We have been studying two populations having an unusually high frequency of Glanzmann disease, Iraqi Jews and Arabs living in Israel, and were able to distinguish the populations on the basis of immunodetectable GPIIIa and platelet surface vitronectin receptor (alpha v beta 3) expression. In this article, we describe molecular genetic studies based on use of the PCR that have allowed us to characterize platelet mRNA sequences encoding GPIIb and GPIIIa from patients in these populations. In six of six Iraqi-Jewish families studied, cDNA sequence analysis identified an 11-base deletion within exon 12 of the GPIIIa gene. This mutation produces a frameshift leading to protein termination shortly before the transmembrane domain of GPIIIa. In contrast, a 13-base deletion encompassing the splice acceptor site of exon 4 of the GPIIb gene was found in three of five Arab kindreds studied. This deletion results in forced alternative splicing to a downstream AG acceptor, producing a 6-amino acid deletion in the GPIIb protein, including a single cysteine residue. These nucleotide sequence variations were exploited to design a rapid, PCR-based oligonucleotide dot-blot hybridization test for both pre- and postnatal diagnosis of Glanzmann disease. These studies demonstrate the heterogeneity of Glanzmann thrombasthenia in different populations, and its homogeneity within geographically restricted populations, and offer insight into the requirements for integrin surface expression.